Interventional left atrial appendage closure may affect metabolism of essential amino acids and bioenergetic efficacy. (1st October 2018) - Rusnak, J.; Behnes, M.; Saleh, A.; Fastner, C.; Sattler, K.; Barth, C.; Wenke, A.; Sartorius, B.; Mashayekhi, K.; Hoffmann, U.; Yuecel, G.; Lang, S.; et al.
Abstract: Background: Interventional closure of left atrial appendage (LAAC) represents an alternative for stroke prevention in patients with non-valvular atrial fibrillation. Whether LAAC may affect metabolomic pathways has not been investigated yet. This study evaluates the impact of LAAC on the metabolism of essential amino acids, kynurenine and creatinine. Methods: Peripheral blood samples of prospectively enrolled patients undergoing successful LAAC were taken before (T0) and 6 months after (T1, mid-term follow-up). Targeted metabolomic profiling was performed using electrospray ionization liquid chromatography–mass spectrometry (ESI-LC-MS/MS) and MS/MS measurements focusing on metabolism of essential amino acids. Results: 44 patients with non-valvular AF (mean CHA2DS2-VASc score 4, mean HAS-BLED score 4) were enrolled. Changes in metabolites of essential amino acids, myocardial contraction and bioenergetic efficacy, such as phenylalanine (percentage change 8.2%, p  = 0.006), tryptophan (percentage change 20.3%, p  = 0.0006), tyrosine (percentage change 20.2%, p  = 0.0001), creatinine (percentage change 7.2%, p  > 0.05) and kynurenine (percentage change 8.3%, p  = 0.0239) were found at mid-term follow-up. Conclusions: LAAC may affect the metabolism of essential amino acids and bioenergetic efficacy. ClinicalTrials.gov Identifier:NCT02985463 Highlights: Successful left atrial appendage closure (LAAC) might affect the metabolism of essential amino acids and kynurenine Pathophysiological alterations due to LAAC include ongoing myocardial contraction, local stretch and device-related neo-endothelization Changes of these metabolites might reveal the impact of LAAC on bioenergetic efficacy